The Effect of Partner Reading Strategy on Reading Comprehension - Yanti Kristina Sinaga; Herman herman; Putri Laura Siahaan (Journal of English Education and Teaching, 2020)
This research is conducted in investigating whether Partner Reading Strategy affects on students’ Reading Comprehension ability in descriptive text. The problem of this research is “What is the effect of Partner Reading strategy significantly for students’ reading comprehension at grade eight of SMP N7 Pematangsiantar?”. To solve the problem of this research, the researchers used related theories ; Grellet (1997), Nunan (1991), Melanie and Paula (2008) and Patel, Jain (2008), Pammun (2017), Snow et al (2002), Dorn and Soffos (2005 ) and Grade (2014). This research was done in SMP N 7 Pematangsiantar. In this research, the researchers conducted an experimental quantitative research. The population of this research was the eight grade of SMP N 7Pematangsiantar The samples of this research were two classes, they were 62students The first class was 31 students of experimental class who had been taught by Partner Reading Strategy and the second was 31 students of control group who had been taught by conventional method. The instrument for collecting the data was 20 items of multiple choice test. The data were analyzed by using t-test formula in order to see whether Partner Reading Strategy significantly affect on students’ reading comprehension or not. The total score of pre-test in control group is 1065, mean 34.35 and the total score of post-test in control group is 1355, mean is 45,16, meanwhile the total score of pre-test in experimental group is1525, mean is 49.19 and the total score of post-test in experimental group is 2470, mean is79.67. The finding indicates that the value of t-test exceeds the value of t-table (8.77> 1,67), at the level of significant p = 0,05 and the degree freedom df= 60. The finding implies that the alternative hypo research is accepted. In other words, there is a significant effect of Partner Reading Strategy on the students reading comprehension.